2020
DOI: 10.1007/s00603-020-02084-5
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanical and Volumetric Fracturing Behaviour of Three-Dimensional Printing Rock-like Samples Under Dynamic Loading

Abstract: Heterogeneous rock contains numerous pre-existing three-dimensional (3D) cracks, which control its mechanical and fracturing properties. Considerable effort has been devoted to studying the volumetric fracturing behaviour of rock under static loading conditions. Although rock masses are often subject to dynamic impacts such as earthquakes and blasting, the mechanical and volumetric fracturing behaviour of rock under dynamic loading is still poorly understood. In this paper, dynamic laboratory tests were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(23 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…5,[194][195][196][197] Therefore, understanding the responses of flawed rocks to engineering disturbances, especially the dynamic strength and dynamic crack propagation characteristics, is essential to guarantee the reliability and safety of engineering projects during construction and operation periods. 5,198 Although rock masses are often subjected to dynamic disturbances, the mechanical and volumetric fracturing behavior of rock under dynamic loading is still poorly understood. This is mainly because the rock dynamics theories are still at its infancy in spite of extensive previous efforts devoted to rock dynamics.…”
Section: Investigation Of Dynamic Crack Propagation In Flawed Rocksmentioning
confidence: 99%
“…5,[194][195][196][197] Therefore, understanding the responses of flawed rocks to engineering disturbances, especially the dynamic strength and dynamic crack propagation characteristics, is essential to guarantee the reliability and safety of engineering projects during construction and operation periods. 5,198 Although rock masses are often subjected to dynamic disturbances, the mechanical and volumetric fracturing behavior of rock under dynamic loading is still poorly understood. This is mainly because the rock dynamics theories are still at its infancy in spite of extensive previous efforts devoted to rock dynamics.…”
Section: Investigation Of Dynamic Crack Propagation In Flawed Rocksmentioning
confidence: 99%
“…Rock structures are frequently subjected to dynamic loads from rock drilling, rock blasting, rock bursts, and seismic events or earthquakes [1][2][3][4]. Under dynamic loads, rock damage or fracture may occur and energy consumption happens [5][6][7]. Accordingly, it is of importance to investigate energy dissipation in the process of rock fracture [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…erefore, the spatial distribution form of double cracks greatly affects the distribution of stress fields around cracks, and the interactive weakening or enhancement effect occurs due to the stress superposition, which has a significant influence on crack initiation and growth characteristics. Moreover, Wong et al, Lu et al, Fu et al, Zhu et al, and Zhou et al have confirmed that the fracture behavior of 3D cracks is significantly different from that of 2D cracks [40][41][42][43][44], which is mainly reflected in the fact that the spatial propagation mode of 3D cracks is more complex, and there are intrinsic limits on 3D propagation of wing cracks, resulting in great change in rock failure mode. In our study, the contribution of mode II and mode III fracture to the 3D crack growth is investigated, and the influence of crack distribution and interaction characteristics is clarified in detail.…”
Section: Discussionmentioning
confidence: 99%